A clinical-molecular update on azanucleoside-based therapy for the treatment of hematologic cancers. Issue 1 (December 2016) - Diesch, Jeannine; Zwick, Anabel; Garz, Anne-Kathrin; Palau, Anna; Buschbeck, Marcus; Götze, Katharina
Abstract The azanucleosides azacitidine and decitabine are currently used for the treatment of acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) in patients not only eligible for intensive chemotherapy but are also being explored in other hematologic and solid cancers. Based on their capacity to interfere with the DNA methylation machinery, these drugs are also referred to as hypomethylating agents (HMAs). As DNA methylation contributes to epigenetic regulation, azanucleosides are further considered to be among the first true "epigenetic drugs" that have reached clinical application. However, intriguing new evidence suggests that DNA hypomethylation is not the only mechanism of action for these drugs. This review summarizes the experience from more than 10 years of clinical practice with azanucleosides and discusses their molecular actions, including several not related to DNA methylation. A particular focus is placed on possible causes of primary and acquired resistances to azanucleoside treatment. We highlight current limitations for the success and durability of azanucleoside-based therapy and illustrate that a better understanding of the molecular determinants of drug response holds great potential to overcome resistance.